Exploring revisit intention behaviour among tourists: empirical evidence from United Arab Emirates tourism industry / Abdul Raheem Jasim Mohamed - Mohamed, Abdul Raheem Jasim (Institute of Graduate Studies, UiTM, 2014)
Tourism has become such an important sector of the economy that the Department of Tourism and Commerce (DTCM) of the United Arab Emirates (UAE) taking the lead to spearhead the promotion of the UAE as an attractive, competitive and memorable tourist destination. The total tourist experience which refers to a multi-faceted exposure during a tourist’s actual visitation to the UAE is argued to be a strong predictor of his or her revisit intention.As tourism image of the UAE is formed from different sources, it is plausible to suggest that a tourist is most likely to form a more complex image of the UAEas a result of either favourable or unfavourable experience